Post-crisis economic environment of two Central and Eastern European regional centres: A comparative approach - Zsuzsanna Zsibók; Ildikó Egyed (Comparative Economic Research. Central and Eastern Europe, 2022)
Our research studies the economic background of recovery and catching-up after the global financial and economic crisis, comparing the case study areas of Cluj-Napoca in Romania and Pécs in Hungary. We use explorative statistical data analysis to describe the post-crisis regional economic environment in the context of the differential outcomes of the high-pressure economy in these two countries. Then, we analyse the evolution of the per capita gross domestic product in a decomposed form which provides insights into the main challenges of regional development in the two regional centres. The results show that long-run economic challenges must be handled with an efficiency-oriented regional policy that relies upon capital and knowledge-intensive growth.
Keywords: O47; P25; R12; 330; regional development; economic growth; Hungary; Romania; comparative analysis